1980
DOI: 10.1080/00222895.1980.10735226
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Difference in Rotary Pursuit Performance

Abstract: This study examined the hypothesis that male dominance in the acquisition and performance of rotary pursuit skill reflects a lower male proclivity for the generation and accumulation of reactive inhibition rather than some innately superior ability to profit from practice. On this hypothesis, the magnitude of male dominance should decline as the length of the intertrial interval increases. The experimental sample consisted of 120 Caucasian subjects (60 of each sex) who were given sixty 30-sec trials on rotary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…On the same hypothesis it was also predicted that the well-known male dominance in rotary pursuit performance would disappear under highly distributed practice conditions. This, too , has been confirmed (McBride & Payne, 1980 , 1979). Perhaps because of the limited sampling opportunities that prevail at most experimental sites, studies of the generality of reminiscence tendencies across races are not available in the psychomotor literature.…”
supporting
confidence: 50%
“…On the same hypothesis it was also predicted that the well-known male dominance in rotary pursuit performance would disappear under highly distributed practice conditions. This, too , has been confirmed (McBride & Payne, 1980 , 1979). Perhaps because of the limited sampling opportunities that prevail at most experimental sites, studies of the generality of reminiscence tendencies across races are not available in the psychomotor literature.…”
supporting
confidence: 50%
“…One explanation for this observation is that males possess some inately superior ability to profit from practice. However, McBride and Payne (1980) have recently demonstrated that male dominance in rotary pursuit skill appears to be a procedural effect mediated by an internal inhibitory mechanism. That is, males have a lower proclivity for the generation and accumulation of reactive inhibition, or in this case the action decrement (Walker, 1958).…”
Section: Discussionmentioning
confidence: 97%
“…Sex differences in RP skills tend to be absent among children in kindergarten through eighth grade (Ammons, Alprin, & Ammons, 1955;Davol & Breakell, 1968;Davol, Hastings, & Klein, 1965;Horn, 1975;Ruffer, 1984;Simensen, 1973; but see Dunham, Allan, & Winter, 1985). By high school and young adulthood, men perform better than women with respect to time on target (Ammons et al, 1955;Archer, 1958;Buxton & Grant, 1939;Cox 1983;Dietrich & Payne, 1985;Huang & Payne, 1975;Jones & Ellis, 1962;Mastroianni & Schopper, 1986;McBride & Payne, 1980;Noble, 1970;White, 1991;Wisner, Lombardo, & Catalano, 1988). In a metaanalysis of different perceptual-motor tasks, the tendency for sex differences in RP to emerge at puberty has been confirmed (Thomas & French, 1985, 1987.…”
mentioning
confidence: 93%
“…In those studies, primarily sex differences in reminiscence and learning have been addressed. Reminiscence is defined as an improvement in performance that occurs after a rest period, and is greater in adult females than in adult males in the RP task (Buxton & Grant, 1939;Dietrich & Payne, 1985;Huang & Payne, 1975;McBride & Payne, 1980;Payne & have often been reported in those studies. Sex differences in RP skills tend to be absent among children in kindergarten through eighth grade (Ammons, Alprin, & Ammons, 1955;Davol & Breakell, 1968;Davol, Hastings, & Klein, 1965;Horn, 1975;Ruffer, 1984;Simensen, 1973; but see Dunham, Allan, & Winter, 1985).…”
mentioning
confidence: 97%